Numerical simulation and experimental verification of heating performance of an integrally water-heated tool. (April 2016) - Abdalrahman, Rzgar; Grove, Stephen; Kyte, Adam; Rizvi, Md Jahir
Design and manufacturing of composite tooling are crucial in producing cost effective composite components with high quality. Aimed at identifying the optimal design of integrally heated tools in terms of their thermal performance, a number of design variables were investigated numerically in a previous study. Statistical analysis of the simulation results revealed that a parallel layout of heating channels can significantly improve the heating performance, and channel separation should be determined according to the production requirement. In the present work, an integrally water-heated tool is manufactured according to the optimal design after some geometry amendments. Thermal properties of the constituent materials of the produced tool are also measured. A numerical model of the tool geometry is simulated with actual material properties and boundary conditions to calculate the response variables of temperature uniformity and heating rate. The numerical results are verified by experimental testing, using a thermal camera and thermocouples. Good agreement between the simulation and the experimental results confirmed the suitability of numerical simulation in predicting the thermal performance of integrally heated tooling and the validity of the boundary conditions.